FACTORS RELATED UTERINE MIOMAS (UTERINE FIBROIDS) AT RSUP DR. MOHAMMAD HOESIN PALEMBANG - Amanda Moeza Fadillah; Rizal Sanif; Indri Seta Septadina (Majalah Kedokteran Sriwijaya, 2022)
Background: Uterine fibroids or uterine myomas are benign tumors cell myometrial smooth muscle surrounded by a pseudocapsule. Uterine fibroids occur in reproductive age women and will slowly disappear at menopause. Uterine fibroids are the second most common reproductive problem experienced by women in Indonesia after cervical cancer. The world incidence rate of uterine myomas is 20-35%, while Indonesia ranges from 2.4% to 11.7%. The study was conducted to know related factors with incident of uterine myomas at RSUP Dr. Mohammad Hoesin Palembang. Methods: This research is an analytic observational study with a cross-sectional approach. The sample of this study were gynecological patients at RSUP Dr. Mohammad Hoesin Palembang and data collected for the period January 2020 - July 2021 that met the inclusion criteria and exclusion criteria. Results and Conclusions: From 60 patients, the proportion of patients with uterine myomas was 61.7%. The analysis using the Chi-square test showed that age ( p = 0.005) had a significant relationship with the incidence of uterine myomas. The results of the analysis using the Chi-square test showed that age at menarche ( p= 1.00), parity ( p= 0.761), body mass index ( p =0.559), infertility ( p =0.112), history of hypertension ( p =1.00 ), history of diabetes mellitus ( p = 1.00), history of using hormonal contraception ( p = 0.634) did not have a significant relationship with the incidence of uterine myoma. Conclusion of this study is the mostr related factors of uterine myomas is age factor.